Role of Facebook as a disaster communication media. Issue 2 (5th August 2019) - Jayasekara, Prasadi Kanchana
Abstract : Purpose: The purpose of this paper is to identify the types of contents shared through Facebook during different phases of disaster management. Design/methodology/approach: The primary data of this study were collected using the qualitative method. To acquire the necessary data, researcher selected 50 Sri Lankan Facebook users who can read and understand Sinhala with more than 1, 000 friends using the snowball sampling method. Selected Facebook users had to collect Facebook posts related to flood during two weeks time period. Data were collected until it reached data saturation point. The collected Facebook posts were transcribed and translated into English. Thematic analysis was used to analyze the Facebook posts. Findings: The most prominent use of Facebook for disaster communication can be observed in, during and post-disaster phases. In the during-disaster phase, people used Facebook to share posts related to disaster warning, request for help or rescue, share information about rescue missions, share contact numbers of rescue teams, request donation items, coordinate aid distribution, ask for volunteer work and to provide feedback about the ongoing funding programs. In the post-disaster phase, people used Facebook to request volunteer help for cleaning, to provide feedback about the progress and to ask about donating cleaning products. Originality/value: Findings of this study can be used by the government or authorized bodies to develop official social media channels, which would fulfill information requirements during disaster situations.